Design Method and Experimental Study of Water-Blocking Special-Shaped Wire Conductor for Submarine Cable - Wenchao WANG; Chi XUE; Ming HU; Youlin ZHAO; Shuhong XIE; Haiyang WANG; Cheng Ye; Ying NIE (Zhongguo dianli)
The design and manufacture of water-blocking conductor is one of the key research topics in field of submarine cable. A new theoretical design method is proposed for trapezoidal wire water-blocking conductor with structures of constant cross section, which has strong versatility and high programmability, suitable for design and manufacturing of water-blocking conductor with a cross-section ranging from 50 mm2 to 3500 m2. The problems such as difficult design & manufacturing and unreasonable conductor size could be solved, with a filling coefficient of conductor reaching more than 0.96. Then, the rationality of the theoretical design method and manufacturing process is verified through water-blocking, mechanical and electrical performance tests. The trapezoidal wire conductor structure has no adverse effect on the cable’s overall performance, and the water-blocking glue conductor is better than that of the water-blocking tape structure. Finally, according to theoretical calculation, the outer diameter of the trapezoidal wire conductor for medium voltage submarine cables designed with the proposed method are 3.9% ~ 7.0% smaller than that of compact circular conductor, which can reduce the manufacturing cost by 1.1%. With the larger conductor cross-section, the structure optimization is more significant, which verifies the economy of submarine cables with trapezoidal wire conductor structure.